(untitled) (Advances in Military Technology, 2022)
The paper is based on previous work of the authors, presented e.g. in [1]. The area of authors’ interests is based on numerical solutions of electrical, magnetic or mechanical fields. The well known numerical methods are Finite Elements and Boundary Elements. Application of these can be successfully done in special technologies or special equipment as high-torque low-speed machine suitable for manipulators or robots working in dangerous and aggressive environment, high-speed bearingless actuators designed for aggressive and explosive surroundings, as well as design and optimization of bridges, pontoons, etc. The bases of the Finite Element Method (FEM) and overview of the authors’ most important results in this field of interest is presented in the following chapters. The used mathematical apparatus leads to identical compatible results which are independent from the used platform of computer application software.